Pemberian Makanan Tambahan Modifikasi Terhadap Status Gizi Balita - Mamik Ratnawati; Ririn Probowati; Septi Fitrah Ningtyas; Ana Farida Ulfa; Monika Sawitri Prihatini (Jurnal Health Sains, 2023)
The occurrence of malnutrition in children is not only due to the nutritional content of the food served, but also caused by the occurrence of health problems, so that the ability to endure and dream of eating will be reduced and susceptible to disease so that the child can experience malnutrition. The purpose of this study was to compare the nutritional status of children under five before and after being given a modified supplementary diet. The research method uses a quasi-experimental research design with pre-test - post-test design with treatment. The sample is a number of toddlers in Puton Village, Diwek District, Jombang Regency. The study was conducted for 4 weeks by providing additional modified food to toddlers with nutritional problems. The sample by means of total sampling. The dependent variable in this study is the ability to provide additional modified food, the independent variable is the nutritional status of children under five. Data analysis using t-test. The results showed that most (70%) nutritional status of children under five improved after being given additional modified food. This study is expected to provide knowledge about other modified food additives and the intervention time of 4 weeks is not optimal enough to improve the nutritional status of toddlers so that it takes a longer time for this intervention to get maximum results.